Application of Bio-Based Epoxy Resin Synthesized from Eugenol in Composites Reinforced with Flax, Nettle, and Basalt Fabrics - Danuta Matykiewicz; Beata Dudziec; Mateusz Barczewski; Adam Piasecki (Journal of Natural Fibers)
The main aim of the study was to evaluate the use of bio-based epoxy resin obtained from eugenol derivatives as a matrix in reinforced composites with flax, nettle and basalt fabrics. Triethylenetetramine (TETA) and isophoronediamine (IDA) were used as curing agents. For the bio-based epoxy monomer, the dynamic viscosity was determined at different temperatures. Fourier-Transform Infrared (FTIR) confirmed the chemical structure of cured composites. The morphology of the composites was assessed by scanning electron microscopy (SEM). The differential scanning calorimetry (DSC) method was used to evaluate the glass transition temperature of composites. Thermal stability was measured by thermogravimetric analysis (TGA) connection with an FTIR spectrometer. Studies confirmed that the eugenol-based resin can be used for the impregnation of natural fiber and the preparation of composite materials. The composites were characterized by multi-stage thermal decomposition confirmed by TGA analysis and low degradation rate determined from DTG curves. The thermal stability of the tested composites with flax and nettle fabrics was on average 235°C, while with basalt fabric it was about 270°C. Composites cured with TETA showed a glass transition temperature Tgof 47.0°C on average compared to composites cured with IDA that showed a Tg of 54.0°C.